Cryptocurrency - Petrová, Lucie; Čajka, Radek, 1983-; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Bitcoin, the first decentralized cryptocurrency, has been around since 2009. Not long afterward, it was followed by a rise of a variety of other cryptocurrencies. Some have gained momentum, some have disappeared. Nonetheless, based on the development thereafter, their future still remains unclear. The main objective of this bachelor thesis is to investigate the future outlook for cryptocurrencies. Is Bitcoin doomed to fail? And if so, what does the future hold for alternative cryptocurrencies and for cryptocurrency in general? This paper aims to answer these questions in three chapters. The first part introduces the main features of cryptocurrencies and gives an overview of how they work. The second part focuses on the most prominent one, namely Bitcoin, analyzing its strengths with a particular emphasis on its weaknesses. The third part strives to draw conclusions on the future prospects of cryptocurrency, while explaining why Bitcoin will not be the future currency, but cryptocurrency might be.
Vedoucí práce: Radek Čajka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses